Measurement of sheath expansion in plasma source ion implantation - Kim, YW; Kim, GH; Han, S; Lee, Y; Cho, J; Rhee, SY (ELSEVIER SCIENCE SA, 2001)
In plasma source ion implantation (PSII), the temporal and spatial sheath evolution in terms of the applied negative pulse on a planar target was investigated using a Langmuir probe. Experiments revealed that the dynamic sheath consists of three parts with respect to the phases of the pulse. (i) An ion-matrix sheath expansion scaled with the square root of pulse rise rate and the supersonic velocity during the pulse rise-time. (ii) A sheath expanding with the order of the ion sound speed in the flat-top phase of the pulse. And finally, (iii) sheath shrinking in the fall-time of the pulse. It was also observed that the ion wave was propagated into the plasma after the flat-top phase of the pulse. (C) 2001 Published by Elsevier Science B.V. All rights reserved.
Keywords: SURFACE MODIFICATION